HmsB enhances biofilm formation in Yersinia pestis - Fang, Nan; Qu, Shi; Yang, Huiying; Fang, Haihong; Liu, Lei; Zhang, Yiquan; Wang, Li; Han, Yanping; Zhou, Dongsheng; Yang, Ruifu (Frontiers in Microbiology, 2014)
The hmsHFRS operon is responsible for biosynthesis and translocation of biofilm matrix exopolysaccharide. Yersinia pestis expresses the two sole diguanylate cyclases HmsT and HmsD and the sole phosphodiesterase HmsP, which are specific for biosynthesis and degradation, respectively, of 3’,5’-cyclic diguanosine monophosphate (c-di-GMP), a second messenger promoting exopolysaccharide production. In this work, the phenotypic assays indicates that Y. pestis sRNA HmsB enhances the production of c-di-GMP, exopolysaccharide, and biofilm. Further gene regulation experiments disclose that HmsB stimulates the expression of hmsB, hmsCDE, hmsT, and hmsHFRS but represses that of hmsP. HmsB most likely acts as a major activator of biofilm formation in Y. pestis. This is the first report of regulation of Yersinia biofilm formation by a sRNA. Data presented here will promote us to gain a deeper understanding of the complex regulatory circuits controlling Yersinia biofilm formation.